ChemInform Abstract: Application of Zirconacyclopentadienes (Metalla‐Heterocycles) and Cross‐Coupling for the Convenient Preparative Method of 6, 13‐Disubstituted Pentacene. Issue 16 (28th March 2013) - Jia, Zhiying; Li, Shi; Nakajima, Kiyohiko; Kanno, Ken‐ichiro; Song, Zhiyi; Takahashi, Tamotsu
Abstract Diiododihydropentacene (II) is used for the introduction of substituents at position 6 and 13 via standard C—C cross‐coupling reactions.